RESPOSTA DO EXTRATO DA ESPÉCIE SHINUS LENTISCIFOLIUS AO ESTRESSE OXIDATIVO - Lohmann, Larissa Vilma; Moreira, Bárbara; Corrêa, Jéssica B.; Gehrke, Ilaine Teresinha Seibel; Heck, Thiago Gomes; Montagner, Greice (Salão do Conhecimento, 2017)
Projeto de Pesquisa